What’s in a name? Unpacking ‘Community Blank’ terminology in reproductive, maternal, newborn and child health: a scoping review - Brynne Gilmore; Özge Tunçalp; Anayda Portela; Debra Jackson; Sanghita Bhattacharyya; Sara Dada; Aoife De Brún; Olive Cocoman (BMJ Global Health, 2023)
Introduction Engaging the community as actors within reproductive, maternal, newborn and child health (RMNCH) programmes (referred to as ‘community blank’) has seen increased implementation in recent years. While evidence suggests these approaches are effective, terminology (such as ‘community engagement,’ ‘community participation,’ ‘community mobilisation,’ and ‘social accountability’) is often used interchangeably across published literature, contributing to a lack of conceptual clarity in practice. The purpose of this review was to describe and clarify varying uses of these terms in the literature by documenting what authors and implementers report they are doing when they use these terms.Methods Seven academic databases (PubMed/MEDLINE, Embase, CINAHL, PsycINFO, Scopus, Web of Science, Global Health), two grey literature databases (OAIster, OpenGrey) and relevant organisation websites were searched for documents that described ‘community blank’ terms in RMNCH interventions. Eligibility criteria included being published between 1975 and 1 October 2021 and reports or studies detailing the activities used in ‘community blank.’Results A total of 9779 unique documents were retrieved and screened, with 173 included for analysis. Twenty-four distinct ‘community blank’ terms were used across the documents, falling into 11 broader terms. Use of these terms was distributed across time and all six WHO regions, with ‘community mobilisation’, ‘community engagement’ and ‘community participation’ being the most frequently used terms. While 48 unique activities were described, only 25 activities were mentioned more than twice and 19 of these were attributed to at least three different ‘community blank’ terms.Conclusion Across the literature, there is inconsistency in the usage of ‘community blank’ terms for RMNCH. There is an observed interchangeable use of terms and a lack of descriptions of these terms provided in the literature. There is a need for RMNCH researchers and practitioners to clarify the descriptions reported and improve the documentation of ‘community blank’ implementation. This can contribute to a better sharing of learning within and across communities and to bringing evidence-based practices to scale. Efforts to improve reporting can be supported with the use of standardised monitoring and evaluation processes and indicators. Therefore, it is recommended that future research endeavours clarify the operational definitions of ‘community blank’ and improve the documentation of its implementation.